Aborto en Melilla: barreras de océano y frontera - Eva Estévanez Jiménez; Maite Cruz Piqueras (Elsevier, 2024)
Resumen: Objetivo: Describir el recorrido que realizan las mujeres para abortar en Melilla, así como identificar y analizar las barreras para su acceso. Método: Investigación cualitativa con un total de ocho entrevistas semiestructuradas realizadas durante 2022 a tres personas referentes en el tema del aborto de ámbito nacional y a cinco profesionales del Área de Salud de Melilla implicadas tanto en la prestación como en el recorrido que hacen las mujeres para poder abortar. El marco teórico que se siguió fueron las barreras de acceso al aborto y los derechos sexuales y reproductivos. Se realizó un análisis temático del contenido y por categorías según las dimensiones del estudio. Resultados: Se han identificado varias barreras de acceso al aborto en Melilla, entre las que destacan la objeción de conciencia, la localización geográfica de Melilla, la situación irregular de las mujeres marroquíes y la necesidad de consentimiento en las menores de 16 y 17 años. Estos obstáculos obligan a las mujeres que quieran abortar a trasladarse a la Península para conseguir el procedimiento, a continuar con un embarazo no deseado o, en el peor de los casos, a someterse a un aborto clandestino en Marruecos poniendo en riesgo su vida. Conclusiones: Las barreras de acceso descritas suponen una vulneración y una violación del derecho al aborto en Melilla. Se debe revisar el recorrido que se ven obligadas a hacer las mujeres de forma que se facilite el acceso y se garantice el derecho a un aborto seguro a todas las mujeres residentes en Melilla. Abstract: Objective: To provide insights into the challenges faced by women seeking abortion services in Melilla, Spain. It seeks to describe the journey these women undertake and to identify and analyze the barriers they encounter in accessing abortion care. Method: A qualitative research approach was employed, involving a series of eight semi-structured interviews during 2022. Three interviews were conducted with national experts in the field of abortion, while five interviews were conducted with healthcare professionals from the Melilla Health Area who are directly involved in providing abortion services and supporting women throughout the process. The study was guided by a theoretical framework that focuses on barriers to abortion access and sexual and reproductive rights. The collected data was analyzed using content analysis and categorized based on key dimensions of the study. Results: The study identified several significant barriers to abortion care access in Melilla. These include conscientious objection among healthcare providers, the geographical remoteness of Melilla, the legal challenges faced by Moroccan women due to their irregular status, and the requirement of parental consent for minors aged 16 and 17. Consequently, women seeking abortion services are forced to travel to mainland Spain, continue with undesired pregnancies, or resort to unsafe clandestine abortions in Morocco, thereby endangering their lives in the worst cases. Conclusions: The barriers to abortion access identified in this study represent a violation of women's reproductive rights in Melilla. Urgent action is required to review the current process, ensuring that access is improved and the right to safe abortion is guaranteed for all women residing in Melilla.